Potential of Acanthus (Jeruju) for Phytoremediation of Heavy Metal Chromium (Cr) - Alfin Fatwa Mei Afifudin; Esti Tyastirin; Rony Irawanto (Indonesian Journal of Biology Education, 2022)
Aquatic plants are plants that have freshwater habitats that have the potential as phytoremediators or managers of pollutants or waste in the waters. One of the aquatic plant species with “emerging” habitat is Acanthus or with local name “jeruju”. The genus Acanthus in Purwodadi Botanical Gardens has two species, there are A. ilicifolius and A. montanus. This research is a Range Finding Test (RFT) to know the limitations of Acanthus to absorb heavy metal chromium (Cr). This research is an experimental research, which was done on March 26 and April 7, 2021, in Purwodadi Botanic Garden's Greenhouse, with four concentration variations, which were 0 mg/L, 1 mg/L, 3 mg/L, and 5 mg/L. The results showed that Acanthus ilicifolius and Acanthus montanus have the potential to be used as phytoremediation plants for heavy metal chromium (Cr) with maximum concentration 5 mg/L